The Effect of Service Quality on Patient Satisfaction at Watusongu Public Health Center, Ulubongka District - Tido, Misla; Indriani Ibrahim , Andi; Sipatu , Lindanur; Matalatta, Wisra; P. Adam, Rosida (Universitas Muhammadiyah Pontianak, 2026)
Patient satisfaction is a key indicator of healthcare service quality, yet service deficiencies remain at Watusongu Community Health Center. This study examined the effect of service quality on patient satisfaction. A quantitative survey was conducted involving 67 patients using structured questionnaires, and the data were analyzed through simple linear regression. The results revealed that service quality has a positive and significant effect on patient satisfaction (β = 0.696, p < 0.001; R² = 0.484). These findings indicate that improvements in tangibles, reliability, responsiveness, assurance, and empathy can enhance patient satisfaction. The study recommends continuous quality improvement in primary healthcare services.